2009
DOI: 10.1128/jcm.01268-08
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium canettii ” Isolated from a Human Immunodeficiency Virus-Positive Patient: First Case Recognized in the United States

Abstract: We report the first case of tuberculosis caused by "Mycobacterium canettii" recognized in the United States. The pathogen was isolated from the cerebrospinal fluid of a 30-year-old Sudanese refugee. CASE REPORTA 30-year-old female Sudanese refugee was admitted to a Baltimore, MD, hospital in January 2005 with advanced AIDS complicated by prior episodes of pneumonia and a reported history of treated tuberculosis. Two months earlier, the patient had been admitted to a Kampala, Uganda, hospital for treatment of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…In coming years there should be changes in this conduct because of the challenges encountered by the frequent isolation, in humans, of new species of mycobacteria considered nonpathogenic or even mycobacteria of the TB complex, that show a different sensitivity profile to tuberculostatic agents and to tuberculinic tests. In this case, the use of techniques for isolation, species identification and determination of susceptibility profile is necessary (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In coming years there should be changes in this conduct because of the challenges encountered by the frequent isolation, in humans, of new species of mycobacteria considered nonpathogenic or even mycobacteria of the TB complex, that show a different sensitivity profile to tuberculostatic agents and to tuberculinic tests. In this case, the use of techniques for isolation, species identification and determination of susceptibility profile is necessary (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study by Pinsky and Banaei (31), which describes a real-time PCR for differentiation of the MTC, fails to differentiate M. tuberculosis and M. canettii and is also unable to differentiate between M. africanum, M. microti, M. pinnipedii, and M. caprae. A capability to identify the specific MTC species causing infection is important for determining the appropriate therapeutic regimen for the patient (34).…”
Section: Discussionmentioning
confidence: 99%
“…Cases of human TB caused by M. canettii have now been reported in Europe and America (12). In addition, recent reports have suggested that the number of true cases of TB caused by M. canettii may in fact be underrepresented (15,34). Therefore, an ability to differentiate M. tuberculosis and M. canettii not only is important from a patient treatment perspective but also will provide important epidemiological information for clinicians.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, two members, M. bovis, the causative agent of zoonotic bovine tuberculosis, and M. canettii, an unusual member responsible for rare tuberculosis cases almost always exposed to Africa, are naturally resistant to pyrazinamide, a first-line antituberculous drug (18,34). Therefore, the rapid and reliable identification of MTBC isolates to the species level is of prime importance for timely selection of appropriate patient antibiotic treatment and also for epidemiological and public health considerations (36). Furthermore, various studies have recently identified distinct phylogenetic groupings within the human-adapted members of the MTBC (i.e., M. tuberculosis and M. africanum species), all of which are congruent (2, 5, 10, 14-16, 19, 20, 32).…”
mentioning
confidence: 99%